Mental retardation associated with "balanced" chromosome rearrangements. - Funderburk, S J (1977)
Balanced chromosome rearrangements were found in seven of 455 retarded children vs. four of 1,679 nonretarded, psychiatric children (P less than .05). The combined incidence of non-Robertsonian balanced rearrangements from this and reported surveys of the mentally retarded was five times greater than that from newborn surveys, whereas Robertsonian translocations were not increased among the retarded. The combined data show an increase in de novo rather than familial rearrangements among the retarded; the increase in de novo rearrangements is specifically for non-Robertsonian translocation.